PFM.62 The Evolution of Fetal Cardiac Screening in Fife: 10 years of data from a district general hospital. (9th June 2014) - Russell, H; Clegg, I; Brown, S; Tydeman, G
Abstract : Fetal Medicine in The Victoria district general hospital in Fife has been auditing its fetal anomaly screening since 2002. This audit of 10 years of data shows the development of fetal cardiac screening and we can compare this to FASPs "key indicators/detection rates". In prenatally diagnosed cardiac anomalies an average of 54.2% of women opted to have an amniocentesis performed. There was an average of 3.98 additional appointments per woman with cardiac anomaly (range 1–9). Over the 10 years the numbers of cardiac anomalies that we are diagnosing has risen – not due to an increase in incidence but due to the evolution of cardiac screening, improvement in ultrasound techniques and machines. From 2009–2012 we have consistently met the FASP target of prenatally diagnosing 50% of cardiac anomalies. Outcome: A total of 119 cardiac anomalies occurred from 2002–2012 in Fife. 16 patients had a TOP, 1 IUD, 82 livebirths and 3 NND (no data from 2002–2006 on 17 patients). Reference: http://www.screening.nhs.uk/fetalanomaly-scotland